Fällfångstdata för mindre vinbärsbrunmal, Euhyponomeutoides albithoracellus, för identifiering av artens sexualferomon - Svensson, Glenn; Anderbrant, Olle; Löfstedt, Christer; Jirle, Erling; Hellqvist, Sven; Öberg, Elisabeth (Swedish National Data Service, 2022)
Data on number of male currant bud moths captured in traps baited with candidate compounds of the sex pheromone of the species. Experiments were performed in black currant orchards in northern Sweden in 2004, 2005 and 2022. Catch of males of the currant bud moth as part of the identification of the sex pheromone of the species. Traps were baited with sex pheromone candidate compounds produced by females and found to be antennally-active in males. Data på antalet hanar av mindre vinbärsbrunmal fångade i fällor betade med olika kandidatsubstanser för artens sexualferomon. Försök utfördes i svartvinbärsodlingar i norra Sverige 2004, 2005 och 2022. Fällfångst av hanar av mindre vinbärsbrunmal för identifiering av artens sexualferomon. Fällor betades med olika kandidatsubstanser producerade av honor och som gav elektrofysiologiska svar i antennerna hos hanarna.